Complementary impacts of small rodents and semi‐domesticated ungulates limit tall shrub expansion in the tundra. Issue 1 (25th November 2013) - Ravolainen, Virve T.; Bråthen, Kari Anne; Yoccoz, Nigel G.; Nguyen, Julie K.; Ims, Rolf A.; Pärt, Tomas
Summary While shrubs appear to be expanding in Arctic tundra due to climatic warming, patches of tall shrubs in riparian habitats are most likely to colonize new areas. Shrub recruits outside established patches represent the forefront of area expansion, but their dynamics may be sensitive to the action of several herbivore species. The empirical evidence for how different‐sized herbivores affect recruits of tall shrubs is lacking. Moreover, although management and natural population dynamics of herbivores happens at landscape and regional scales, field research on herbivore impacts on shrubs seldom covers these scales. Reindeer management and different rodent population dynamics result in regional variation in herbivore abundances in arctic Norway. We conducted an herbivore exclusion experiment, covering three low‐arctic river catchments with contrasting herbivore abundances. We assessed the impacts of small rodents and reindeer on growth, and survival of willow Salix spp. recruits after 3 years of herbivore exclusion. As expected, the Salix recruits increased in sizes and had lower mortality when released from herbivores. Both types of herbivores had strong impacts on size and survival of Salix recruits. Spatially contrasting results were consistent with regional differences in the abundance of reindeer and rodents; herbivore impacts on shrubs were found when at least one type of herbivore was abundant. However, the impact was not independent of herbivore species. While both browsing from reindeer and rodents pruned the recruits and prevented them from escaping the field layer, the rodents also inflicted substantial mortality and thus thinned the stand of recruits. Synthesis and applications. Sympatric populations of rodents and reindeer have strongly complementary impacts on shrub recruits and may limit the expansion potential of tall shrubs even in the most productive habitats of arctic tundra. The spatial correspondence between shrub recruits performance and herbivore abundances, found after a short time period, suggests that the extent of tall shrub expansion in tundra is contingent on current variation and future trends in herbivore populations. In areas where humans control large herbivore populations, management may opt to counteract climate‐driven shrub expansion also in habitats that are most prone to such expansion.